Growth of diazonium-functionalized ZnO nanoflakes on flexible carbon cloth for electrochemical sensing of acetone in the liquid phase. Issue 17 (13th April 2023) - Abbas, Azhar; Mansoor, Seemal; Nawaz, Mian Hasnain; Chaudhry, Aqif Anwar; Ijaz, Kashif; Riaz, Sara; Hayat, Akhtar
Abstract : Growth of diazonium functionalized ZnO Nanoflakes on flexible carbon cloth and evaluation of the synthesised sensor for simple, sensitive and selective detection of acetone in liquid phase. A wide working range (0.1–2000 ppm) and low detection limit (0.03 ppm) were achieved. Abstract : Simple detection of acetone is indispensable due to its health and environmental concerns. Surface-modified electrodes are promising for the detection of acetone. In the present study, the facile fabrication of ZnO nanoflakes on carbon cloth (CC) is reported. The electrode was fabricated by decorating the CC with ZnO nanoparticles (ZnO NPs), followed by the hydrothermal treatment and modification with diazonium salt using linear sweep voltammetry (LSV) forming ZnO nanoflakes (ZnO NFs) on ZnO NPs/CC. The as-prepared ZnO/CC electrode was used for the detection of acetone at room temperature using cyclic voltammetry. Fourier transform infrared spectroscopy (FTIR), atomic force microscopy (AFM), scanning electron microscopy (SEM), X-ray diffraction (XRD), and Brunauer–Emmett–Teller (BET) analyses were used for the chemical and physical characterization of the CC before and after each modification step. The obtained data manifested that ZnO NFs functionalized with diazonium salt increased the roughness of the CC surface, which was advantageous to promote the interaction between CC and acetone target. The modified sensing platform showed excellent performance in terms of the wide working range (0.1–2000 ppm) and low detection limit (0.03 ppm), making it a promising and cost-effective sensor of acetone in the liquid phase.